2006
DOI: 10.1007/s00262-005-0118-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor progression despite massive influx of activated CD8+ T cells in a patient with malignant melanoma ascites

Abstract: Although melanoma tumors usually express antigens that can be recognized by T cells, immune-mediated tumor rejection is rare. In many cases this is despite the presence of high frequencies of circulating tumor antigen-specific T cells, suggesting that tumor resistance downstream from T cell priming represents a critical barrier. Analyzing T cells directly from the melanoma tumor microenvironment, as well as the nature of the microenvironment itself, is central for understanding the key downstream mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 27 publications
5
107
1
1
Order By: Relevance
“…We detected the presence of suppressor/regulatory T lymphocytes and tolerogenic DCs at all stages of melanoma development. FOXp3-positive, IL-10 producing T lymphocytes were recently reported in tumour, blood and ascites from patients with advanced melanoma, and were associated with melanoma-related immunosuppression (Appay et al, 2006;Cesana et al, 2006;Harlin et al, 2006). As well as FOXp3 we have also demonstrated expression of ILT3, a marker of tolerogenic DCs and have correlated markers of local immunosuppression with melanoma progression.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We detected the presence of suppressor/regulatory T lymphocytes and tolerogenic DCs at all stages of melanoma development. FOXp3-positive, IL-10 producing T lymphocytes were recently reported in tumour, blood and ascites from patients with advanced melanoma, and were associated with melanoma-related immunosuppression (Appay et al, 2006;Cesana et al, 2006;Harlin et al, 2006). As well as FOXp3 we have also demonstrated expression of ILT3, a marker of tolerogenic DCs and have correlated markers of local immunosuppression with melanoma progression.…”
Section: Discussionmentioning
confidence: 57%
“…Indoleamine 2,3-dioxygenase is an enzyme produced mainly by APC of myeloid origin that suppresses T lymphocyte-related antigen-specific immune responses (Mellor and Munn, 2004). It has also been associated with disease progression in various tumour types, including colorectal cancer (Brandacher et al, 2006), haemangioma (Ritter et al, 2003) and melanoma (Harlin et al, 2006).…”
mentioning
confidence: 99%
“…Development of antitumor vaccines often aims at generation of strong antitumor T-cell reactivity (14). Although CTLs are crucial effector cells against cancer, the high frequency of HLA class I antigen down-regulation in malignancies may limit the effectiveness of vaccines aimed at stimulating CTL responses (15,16). In addition, recent studies showed that even a massive influx of activated CD8 + T cells in a patient with malignant melanoma was not sufficient for inhibition of tumor progression (16).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its role in tumor development, the prognostic value of PD-L1 has been studied in several instances and found to be associated with poor prognosis in non-small cell lung cancer, gastric carcinoma, and renal cell carcinoma. 25,26,35 Despite several reports of PD-L1 expression in melanoma, [21][22][23]40 its prognostic relevance in melanoma patients has been suggested only recently. 41 In line with this recent study, the current work addressed whether, in the melanoma setting, PD-L1 expression increases during disease progression and whether its expression correlates with other immunological …”
Section: Til Infiltration Treg Infiltration Tgf-b Mhc-i Expressionmentioning
confidence: 99%